Soja em um vaso de flores: geopolítica dos alimentos e divisão sexual do trabalho na América Latina (1986-2015) - García, Diana María Peña (2021)
This thesis examines if the corporate food regime not only determines the technology, specialization patterns, and financialization of agriculture, but also exacerbates the sexual division of labor as part of the capitalist alienation strategy. A neo-Marxist theoretical framework was adopted to build a bridge between the global and domestic scales. At the global scale, the analysis of Food Regimes delves into the correlations between the territorial division of labor and capital accumulation; at the domestic scale, the social reproduction approach allows us to analyze both the mechanisms of capitalist appropriation of surplus value and the strategies of peasant families to remain in their territories. To discover the role of Latin America in this global arrangement, two cases were contrasted: floriculture in Colombia and soybean production in Brazil. These cases expose the logic of specialization within the geopolitics of food and introduce important reflections on the horizons of capitalist accumulation, food sovereignty, and gender; specifically, a contradictory and combined process of masculinization and feminization of the production of NTCs is evident in the region. These crops are associated with technological packages that determine specific combinations of capital and labor, which, in turn, are a geographic response to the international division of labor. Empirical evidence shows a positive correlation between mechanization and masculinization, with the soybean complex being one of the most striking examples; this masculinization of productive labor and consequent invisibilization of reproductive labor keeps the remuneration of the labor force artificially low. In contrast, the feminization of floriculture in Colombia reveals the mechanisms of exploitation of the most vulnerable population in labor-intensive agribusinesses.